KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI PADA PT BUMI SERPONG DAMAI TBK - Chandra Jaya Varana; Ellen Rusliati (Faculty of Economic and Business, University of Pasundan, 2018)
This research aims to analyze financial performance before and after acquisition of PT Bumi Serpong Damai. Financial performance measured by using financial ratio: Current Ratio (CR), Total Asset Turnover (TATO), Debt Equity Ratio (DER). Methods of analysis using comparative descriptive with paired sample t-test, this research data used are the financial statements of PT Bumi Serpong Damai periodof 2008-2014. The result of this research indicate that there are no differences between the financial perfoermance before and afrter acquisition, as measured by current ratio, total asset turnover, debt equity ratio, and return on equity.